Efeitos da dimerização na estrutura e atividade biológica dos peptídeos antimicrobianos Aureína 1.2 e Magainina 2 - Lorenzón, Esteban Nicolás [UNESP] (2015)
Dimeric versions of the antimicrobial peptides (AMPs) Aurein 1.2 (AU) and Magainin 2 (MG2) were synthesized and evaluated for the influence of dimerization and the position of the linker (N- or C-terminal) in the structure and biological activity. In aqueous solution, AU showed no defined secondary structure. On the other hand, the dimers (AU)2K and E(AU)2 showed a helical structure. In the presence of membrane mimetics, the three peptides acquired a α-helix structure. Preliminary studies of hemolytic activity and leakage of carboxyfluorescein showed that the activity of AU is concentration dependent. However, this effect was less pronounced for the dimeric versions. This suggested that dimerization would change the mechanism of action, a fact that was confirmed by different biophysical techniques (contrast microscopy, isothermal titration calorimetry, circular dichroism and leakage of carboxyfluorescein). Regarding antimicrobial activity, dimeric versions had a marked decrease in activity against Escherichia coli, Staphylococcus aureus e Càndida albicans when compared to the monomer. However, dimers showed the ability to aggregate cells of Candida albicans. Using spectroscopic techniques (circular dichroism and fluorescence), it was shown that (AU)2K interacts with mannans molecules, the main component of the cell wall of C. albicans. This interaction was not observed for the monomer. Based on these results, a model has been proposed by which the dimer interacts with mannans, leading to aggregation of the yeast cells. In a second part, MG2 was studied. In aqueous solution MG2 and the two dimeric versions showed no defined secondary structure. However, in the presence of membrane mimetics, all three peptides have acquired helical structure. The results showed that the N-terminal dimerization did not affect the biological activity of the peptide MG2. On the other hand, the peptide (MG2)2K showed...